(untitled) (Swarnadwar, 2025)
The study examined the entrepreneurial intention and influencing factor of management students in Bhaktapur district of Nepal. Entrepreneurial intention is considered a motivator of entrepreneurial behavior and is often considered the most important component to consider in an entrepreneur’s activity while starting a business. The study examined the factor influencing entrepreneurial intention of management students and relationship between different influencing factor and entrepreneurial intention. A quantitative research method utilizes to analyze the study. The sample size selected for the study is 112 students. The finding revealed that all hypothesis were rejected expect perceived feasibility which stated that highly positive relationship between entrepreneurial intention and perceived feasibility. F-statistics 20.827 with p value less than <0.001 indicates that the regression model was statistically significant. The study highlights the significant role of PF in predicting EI, offering valuable insights for both researchers and practitioners. By addressing the identified limitations and exploring new avenues, future research can build upon our findings to further advance the understanding of this relationship.